CORRELATION BETWEEN NEUTROPHIL-LYMPHOCYTE RATIO WITH GLUCOSE CONTROL IN T2DM PATIENTS - Ardiany, Deasy; Soelistijo, Soebagijo Adi; Novida, Hermina; Pranoto, Agung (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Elevated levels of systemic inflammatory markers are associated with cardiovascular disease (CVD). Neutrophil-Lymphocyte Ratio (NLR) is a widely available, easily derived, inexpensive and reproducible marker of inflammation. The NLR can also be affected by atherosclerotic risk factors, such as diabetes. There is no sufficient data about correlation between NLR and glycosylated haemoglobin (HbA1c). The aim of the present study was to investigate the correlation between NLR with HbA1c in T2DM patients. METHODOLOGY This study was cross-sectional observational design performed at Surabaya tertiary hospital between March until April 2019. Patients who fulfilled the criteria of inclusion and exclusion got their blood pressure, complete blood count, neutrophil, lymphocyte counts, plasma glucose, serum glycosylated hemoglobin, serum creatinine, and plasma albumin measured. Data were statistically analyzed using Pearson Correlation test. RESULTS We enrolled 30 hospitalized T2DM patients consisting of 17 (56.7%) men and 13 (43.3%) women with average age was 54.7 years old (31-74 years old). The mean of systolic blood pressure was 126±17.5 mmHg and diastolic blood pressure was 79,3±9.4 mmHg. The overall mean Hb, WBC and PLT were 9.87±1.7 g/dL, 19,236±6,866.4/ mm3and 399,133±155,125.9/ mm3 respectively, while NLR was 15.01±5.9, random blood glucose 353.73±157.2 mg/dL, HbA1c 9.88±1.9%, and eGFR 62.37±32.4 mL/min/1.73 m2. Statistical analysis showed that there was significance correlation between NLR with HbA1c in T2DM patients in this study (p=0.07; r=0.48). CONCLUSION We concluded that there was significance correlation between NLR and HbA1c in T2DM patients in this study.